PERANCANGAN PORTAL WEB LEGALITAS WEBSITE KOMERSIAL (Design Web Portal for Legality of The Commercial Website) - Hayat, Cynthia; Oktaviani, Mega Putri (DINAMIKA DOTCOM, 2014)
The trade transaction with the internet was not controlled, both from the aspect of the clarity of the law and from each trade tax. Many cases of the deception and damaging dishonesty the customer became the importance reason of a department or the system thatÂ  could arrange the trade that used the internet. The department or this system functioned as the department that misses official permission some website commercial or the legality website commercial.With legality website commercial the was hoped for so that the process of the online trade transaction more orderly and clear his legal rule but also that the government could pull the trade tax from goods or the service. The legality website this could increase the customers trust when they want to do online transaction, reduced the crime rate/dishonesty,and the owner website commercial to obey the tax.Keywords:Â  legality, legality of commercial website, EC-trust